Association between male infertility and the risk of hypertension: A meta‐analysis and literature review. (15th July 2022) - Li, Ya‐Dong; Ren, Zheng‐Ju; Gao, Liang; Ma, Jun‐Hao; Gou, Yuan‐Qing; Tan, Wei; Liu, Chuan
Abstract: To explore the association between male infertility and hypertension risk, a meta‐analysis and systematic review was conducted. Observational studies were sought in Medline, PubMed, EMBASE, Web of Science, and China National Knowledge Infrastructure up to April 30, 2021. Two independent reviewers selected available studies and extracted the data. The association between male infertility and hypertension risk was estimated by calculating the relative risk (RR) and 95% confidence interval (95% CI) using Stata12.0 statistical software. A total of seven studies were included in this meta‐analysis, including 102, 152 patients and 636, 645 healthy individuals. The results demonstrated that male infertility was significantly associated with increased hypertension incidence (RR = 1.08; 95% CI 1.02–1.14; p = 0.004), with moderate‐quality evidence. A subgroup analysis based on region showed that a positive association was observed in Europe but not the United States or Asia. This positive association was further confirmed in a cohort study, but not in a case‐control study. After adjusting for potential confounders, male infertility was still significantly associated with hypertension risk (RR = 1.06, 95% CI 1.03–1.09). In conclusion, our findings suggest that male infertility increases the risk of hypertension incidence. However, further studies are needed to provide more conclusive evidence.